Vein of Galen Aneurysmal Malformations: An Ultrasonographic Incidental Finding—A Case Report. (1st November 2012) - Stephan, S.; Rodesch, G.; Elolf, E.; Wiemann, D.; Jorch, G.
Abstract : Background . The Vein of Galen aneurysmal malformation (VGAM) is a rare congenital, cerebral, arteriovenous deformity. Good cross-discipline cooperation is in demand because of associated complications and high mortality. The recognition of the optimal therapeutic window is useful to allow proper management. Case Report . We report on the successful treatment of a 2-week-old, healthy girl with a VGAM, which came across in the context of the newborn ultrasonographic screening. After interdisciplinary discussion, 2 embolizations of the VGAM followed without complications—the first in the age of 6 months and the second at 12 months of life. Before and after the intervention, the patient had an age-appropriate development without neurological deficits. Conclusion . The endovascular transarterial embolization is described as the treatment of choice. Time and method of intervention depend on clinical signs of the patient. In our case the patient was asymptomatic. So the arteriovenous abnormality was an incidental finding by ultrasound. Because of the natural history of the disease, and the potential severe neurocognitive consequences at long-term followup if left untreated, it was decided to embolize the lesion. Thanks to embolization with glue, good therapeutical and clinical results could be obtained with normal neurological development.